2019
DOI: 10.1186/s13012-019-0927-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing cardiovascular disease prevention guidelines to translate evidence-based medicine and shared decision making into general practice: theory-based intervention development, qualitative piloting and quantitative feasibility

Abstract: Background The use of cardiovascular disease (CVD) prevention guidelines based on absolute risk assessment is poor around the world, including Australia. Behavioural barriers amongst GPs and patients include capability (e.g. difficulty communicating/understanding risk) and motivation (e.g. attitudes towards guidelines/medication). This paper outlines the theory-based development of a website for GP guidelines, and piloting of a new risk calculator/decision aid. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 36 publications
(62 reference statements)
0
73
0
Order By: Relevance
“…Further research is needed to determine whether the behavioral outcomes of heart age calculators can be improved by linking it to additional behavior change strategies known to improve lifestyle change (eg, action planning) [ 16 ] and whether absolute risk formats used in clinical practice can be equally engaging [ 28 ]. There is very little research comparing different labels for the general concept of biological age , but one study has found differences in the way that young people interpret heart age compared with fitness age even when the same numerical age result is used [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to determine whether the behavioral outcomes of heart age calculators can be improved by linking it to additional behavior change strategies known to improve lifestyle change (eg, action planning) [ 16 ] and whether absolute risk formats used in clinical practice can be equally engaging [ 28 ]. There is very little research comparing different labels for the general concept of biological age , but one study has found differences in the way that young people interpret heart age compared with fitness age even when the same numerical age result is used [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SMSS can be used to conduct audits and provide feedback to grantees committed to sustaining prevention programs and initiatives once initial funding has ended. are recognized as important for prevention [19,20], much of the relevant science on feedback in health has involved improvement in clinical performance [21][22][23][24][25][26][27]. This includes clinical supervision and use of technology like electronic dashboards in measurement-based quality improvement (MBQI) strategies that monitor patient behavior and clinician activity [28][29][30], while prevention has a more limited history of using computational technologies for monitoring [31][32][33][34].…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…One of the reasons for developing a valid and reliable measure of sustainment is to provide a means of conducting an audit and providing feedback to organizations engaged in implementing innovative and evidence-based programs and practices. While monitoring and feedback are recognized as important for prevention [18,19], much of the relevant science on feedback in health has involved improvement in clinical performance [20][21][22][23][24][25][26]. This includes clinical supervision and use of technology like electronic dashboards in measurement-based quality improvement (MBQI) strategies that monitor patient behavior and clinician activity [27][28][29], while prevention has a more limited history of using computational technologies for monitoring [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%